Expression of insulin-like growth factor family genes in clear cell renal cell carcinoma - Braczkowski, Ryszard; Białożyt, Michał; Plato, Marta; Mazurek, Urszula; Braczkowska, Bogumiła (Contemporary Oncology/Współczesna Onkologia, 2016)
Aim of the study : Despite significant progress in the pathology of clear cell renal cell carcinoma (ccRCC), diagnostic and predictive factors of major importance have not been discovered. Some hopes are associated with insulin-like growth factors. The aim of the study was to compare the expression of genes for insulin-like growth factor family in tumours and in tissue of kidneys without cancer. Material and methods : Fifty-two patients years with clear cell renal cell cancer were qualified to the study group; patients nephrectomised because of hydronephrosis were included in the control group. Expression of genes were evaluated by RT-PCR. Results : Expression of IGFR-1 gene in tumour accounts for about 60% of cases. The incidence is higher than in corresponding adjacent non-cancerous kidney tissues and higher (but with no statistical significance) than in kidney without cancer. Expression of IGFR-2 gene in tumours has not been established. The incidence of the expression in corresponding adjacent non-cancerous kidney tissues is small. Expression of this gene has been present in all specimens from kidneys without cancer. Expression of IGFBP-3 gene ascertained in all (except four) cases of ccRCC and in the majority of clippings from adjacent tissue. It was not found in kidneys from the control group. IGF-1, IGF-2, and IGFR-1 mRNA copy numbers in ccRCC were higher than in the material from the control group